Keengganan Istri Bercerai Dengan Suami Pecandu Narkoba Di Tanjung Pura Langkat - Dinda Syahira; Muhammad Saleh; Abdi Samra (Journal Smart Law, 2025)
Marriage is something almost everyone wants. Surely every married man and woman look forward to enjoying life together. Not all marriages go as expected. There are many problems that can arise in the home. One of the most severe problems is that husbands become drug addicts. A wife who faces this kind of husband is in very difficult circumstances. She had to choose between staying in the house or going out for her own safety and that of her children. She should also consider whether to remain obedient to a husband who is no longer able to care for his responsibilities. This study aims to determine the reasons why wives in Tanjung Pura are reluctant to divorce even though their husbands have become drug addicts. The research methods used are inductive and deductive. The results of the study show that: Children, husbands still provide physical and emotional support, wives still love their husbands, wives still hope their husbands will stop using drugs. These are the factors that cause wives to be reluctant to divorce their husbands in Tanjung Pura. Initially, the marriages of drug addicts were happy and harmonious before the husbands became addicted to drugs. Most marriages were based on love. Some were arranged marriages. They mostly have a high school education and have children, with an average low economic status. Drug addiction is caused by the environment, social circles, economic pressure, and a lack of religious understanding.